Understanding the use intention and influencing factors of telerehabilitation in people with rehabilitation needs: a cross-sectional survey - Wang, Mao-Yuan; Chen, Hong; Gong, Cheng; Peng, Xu-Miao; Zhong, Yan-Biao; Wu, Chun-Mei; Luo, Yun; Wu, Yong-Qiang (Frontiers in Public Health, 2023)
Objective This study aimed to investigate the use intention and influencing factors of telerehabilitation in people with rehabilitation needs. Methods This cross-sectional survey recruited a total of 183 participants with rehabilitation needs from May 2022 to December 2022. Sociodemographic and medical data were collected by a structured questionnaire. The factors influencing the use intention of telerehabilitation were measured by the extended Unified Theory of Acceptance and Use of Technology (UTAUT) model. Multiple hierarchical regression analyses were performed. Results A total of 150 valid questionnaires were included for analysis. The results indicated that the use intention of telerehabilitation was overall high in people with rehabilitation needs. Health condition (β = −0.21, p = 0.03), performance expectancy (β = 0.21, p = 0.01), facilitating conditions (β = 0.25, p = 0.03), perceived trust (β = 0.25, p < 0.01), and self-efficacy (β = 0.19, p = 0.04) were significant factors influencing the use intention of telerehabilitation. Conclusion Overall, the use intention of telerehabilitation is high in individuals with rehabilitation needs. Health conditions, performance expectancy, facilitating conditions, perceived trust, and self-efficacy are important factors influencing the use intention of telerehabilitation in individuals with rehabilitation needs.